Where does decentralised green nitrogen fit in Africa’s fertiliser resilience strategy? - Andrew Nelson; Jun Suk Byun; Eric A. Davidson; Achim Dobermann; Yue Dou; Martin Fregene; Jawoo Koo; Thomas Oberthür; Lorenzo Rosa; Philip Thornton (Food Security, 2026)
Africa faces recurrent fertiliser shocks because much of its nitrogen supply depends on imported products, fossil energy, and exposed trade routes, while production, product mix, logistics, and farm-gate demand remain poorly aligned. Decentralised green nitrogen production – defined as small-scale nitrogen fertilizer synthesis powered by renewable electricity – could make a major contribution to addressing these challenge, but to go to scale it will need to lower delivered costs, improve farm returns, reach farmers with responsive crops, and manage product, safety, resource, and governance risks. This opinion piece argues for an Africa-wide prioritisation assessment that compares potential decentralised production with imports, regional trade, larger low-emission plants, blending, logistics, and advisory support. The goal is to identify intervention bundles that deliver the right nitrogen product to the right farmers at the right cost for the coming decades.